The behavior of polyurethane foam-filled glass-fiber-reinforced polymer crossarm subjected to lightning transient voltage - Rahman M.S.A.; Kadir M.Z.A.A.; Rahman M.S.A.; Osman M.; Amirulddin U.A.U.; Nor S.F.M.; Zainuddin N.M. (MDPI, 2023)
Fiber reinforced plastics; Flashover; Glass fibers; Lightning; Polyurethanes; Power quality; Reinforcement; Wood; Critical flashover voltage lightning impulse voltage; Critical flashover voltages; Cross arm; Electrical stress; Foam filled; GFRP composite crossarm; GFRP composites; Glassfiber reinforced polymers (GFRP); Lightning impulse voltage; Polyurethane Foam; Finite element method